Ferrite toroidal core with a trifilar wound RF broadband transformer design for tracking generators in wideband code division multiple access envelope tracking RFPA systems. Issue 5 (23rd March 2016) - Yusoff, Zubaida; Lees, Jonathan; Chaudhary, Muhammad Akmal; Cripps, Steve C.
Abstract: In this paper, the design of an RF broadband transformer for wideband code division multiple access (WCDMA) tracking generators to be used in envelope tracking RF power amplifiers systems is presented. A ferrite toroidal core with a trifilar wound RF broadband transformer has been chosen to satisfy the (WCDMA) bandwidth requirement and also the power amplifier performance criteria that include the efficiency, electrical isolation, size and power consumption. The design components investigated comprises ferrite materials, number of turns on core windings and size.